Subchronic Toxicity Test of Purple Leaves Ethanol Extract (PLEE) on the Histopathological Picture of the Lymph of Wistar Rats and Antioxidant Activity - Darmayanti; Niluh Puspita Dewi; Mariyani; Joni Tandi; Meike Rachmawati; Yuliet Susanto (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the toxic effects of purple leaf ethanol extract on lymph organs at doses of 500; 2.000; and 5.000 mg/kgBB administered for 28 days and and to determine the antioxidant activity of purple leaf Graptophyllum pictum (L.) This study is an experimental study with a random group design, using 20 test animals divided into 4 groups consisting of two treatment groups, namely in the normal control group given Na-CMC 0.5% and the experimental group given PLEE (k1: dose 500 mg/kgBB, k2: dose 2.000 mg/kgBB and k3: dose 5.000 mg/kgBB hematoxylin-eosin staining (HE) using a computer-connected Motic BA210 microscope with 40X magnification in 5 fields of view and antioxidant test using DPPH method with UV-Vis Spectrophotometer at 516 nm wavelength with concentration 20, 40, 60, 80, and 100 ppm. The results showed that leaf ethanol extract was toxic at a dose of 2.000 mg/kgBB – 5.000 mg/kgBB against the diameter of lymphatic organ pulp, organ index and organ weight, there were symptoms of toxicity and purple leaf ethanol extract had strong antioxidant activity with 66.26 μg/mL.